Zukunftsangst! Fear of (and hope for) the huture and its impact on life satisfaction - Alan Piper (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
The thoughts that an individual has about the future contribute substantially to their life satisfaction in a positive or negative direction. This is a result found via five different methods, some of which control for personality and disposition and the potential endogeneity of thoughts and life satisfaction. The reduction in life satisfaction experienced by individuals who report being pessimistic is greater than that for well-known objective statuses like unemployment. Including individuals' thoughts about the future substantially increases the explanatory power of standard life satisfaction models. Life satisfaction is made up of objective and subjective factors and methods exist to account for their potential endogeneity to enhance our understanding of well-being. This investigation is an example of such an analysis combining a subjective factor, thoughts about the future (treated as endogenous), with more standard objective factors to aid understanding regarding well-being.
Keywords: C23; D84; I31; 330; Life Satisfaction; Subjective Well-Being; GMM; Dynamics; Endogeneity; SOEP; ESS